Modal Intelektual dan Pengungkapan Tanggung Jawab Sosial - Dewi, Ni Putu Krisna; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 31 No 8 (2021), 2021)
Empirical testing of the correlation of intellectual capital and disclosure of social responsibility with, structural capital, customer capital, human capital is the purpose of this study. Companies that are included in the LQ45 list of the Indonesia Stock Exchange for the 2015-2017 period are used as samples in this study, and the purpose sampling method is used to collect samples. Multiple regression analysis technique is used through SPSS to analyze a data. Based on the previous study, it is concluded that human capital positively affects the disclosure of social responsibility, at the same time, neither structure_capital nor customer capital has any impact on the disclosure of social responsibility. The results of this study are in line with resource-based theory, legitimacy theory, and resource dependency theory. These theories believe that every company has different and unique resources, which can add a sustainable competitive advantage to the survival of the company, but companies as organizations rely on Strengths to provide resources and use them in their operations. Keywords: Intellectual Capital; Disclosure of Social Responsibility.